(untitled) (Conference on English Language Teaching, 2025)
The widespread use of generative AI tools such as ChatGPT among university students has introduced new challenges to academic integrity, particularly in the form of hallucinated citations: fabricated references that appear plausible but cannot be verified. This study investigates the effectiveness of a targeted instructional intervention in improving students’ ability to identify and correct such false citations. A total of 139 students applied to participate through online recruitment; 50 were selected, 34 attended the training, and 27 completed both pre- and post-tests. The intervention consisted of a three-hour online session conducted via Zoom, where students were trained in responsible AI use, APA 7th citation formatting, and reference verification techniques. Pre- and post-tests required students to write short literature reviews using AI tools, and their submissions were assessed based on four indicators: the number of hallucinated sources, non-journal citations, reputable journal references, and APA formatting errors. Results revealed a significant reduction in fabricated and low-quality references, along with an increase in the use of reputable sources and improved citation formatting. These findings align with previous research emphasizing the risks of uncritical AI use and the importance of digital literacy education. The study concludes that targeted training is an effective method for mitigating citation hallucinations and enhancing students’ academic writing skills. The research highlights the necessity of integrating AI literacy into academic curricula to ensure ethical and effective engagement with emerging technologies in higher education.